Implementation of Problem Based Learning Based on 4C in Independent Curriculum Science and Social Learning in Elementary Schools - Hardono, Fajar Puji; Yamtinah, Sri; Rintayati, Peduk (Universitas Sebelas Maret, 2024)
The aim of this research is to analyze the implementation of the PBL Based on 4C in Independent Curriculum science and social learning for 5th Grade students at SD Negeri Wirun 01 in Sukoharjo Regency for the 2023/2024 academic year. The teachers who participated were class 5 teachers with more than 10 years of teaching experience. This research was carried out by observing and seeing directly the teacher who was teaching in class. The research method used in this research is a qualitative approach using descriptive methods. Data collection techniques for qualitative research include observation, interviews, and documentation studies. The research results showed that the PBL Based on 4c model can have a positive impact on teachers and students in implementing 21st century learning. Later, the results of this research can support the implementation of 4C which includes Critical Thinking, Creativity, Collaboration and Communication for 5th Grade students, especially in when learning science and science using the independent curriculum.